Method for producing purified carbonized material, purified carbonized material, negative electrode mixture and secondary battery, and method for producing sulfur, and method for producing heavy oil and / or light oil
By using rubber raw materials with high sulfur content and combining heat treatment and separation technology, the manufacturing problem of positive electrode active materials for non-lithium ion type secondary batteries in the prior art is solved, and efficient and low-cost material preparation is achieved, and it is suitable for battery applications such as sodium and potassium.
Patent Information
- Application Number
- JP2024181938
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-10-17
- Publication Date
- 2025-05-01
AI Technical Summary
The prior art is difficult to effectively manufacture positive electrode active materials suitable for non-lithium ion type secondary batteries, especially the application ability of metals such as sodium, potassium and calcium carbonate, and there are problems of difficulty in obtaining materials and high cost.
Rubber with high sulfur content is used as raw material, and fine carbides and heavy oil are obtained through heat treatment and separation processes, and combined with elements such as sodium and potassium to form an active material system suitable for the positive electrode and the negative electrode.
The efficient manufacturing of the positive and negative electrode materials of non-lithium ion secondary batteries is achieved, which reduces material costs, improves material utilization, and expands the scope of application to different metals.
Smart Images

Figure 2025069939000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode active material for a secondary battery and a method for producing an electrode member suitable for the same, and also to a positive electrode mixture and a secondary battery using the electrode member (including the positive electrode active material) obtained by these production methods. The present invention also relates to a method for producing a refined carbide using sulfur-containing rubbers as a raw material, the refined carbide obtained by this production method, and a negative electrode mixture and a secondary battery using the refined carbide. The present invention also relates to a method for producing sulfur using sulfur-containing rubbers as a raw material, a method for producing heavy oil and / or light oil, and a method for treating sulfur-containing rubbers. [Background technology]
[0002] Demand for lithium secondary batteries has been increasing in recent years as small power sources for mobile phones, etc., and medium- and large-sized power sources for electric vehicles, power storage, etc. However, lithium, the main constituent element of the positive electrode active material of lithium secondary batteries, can only be produced profitably from salt lakes in a limited number of countries, raising concerns about supply instability and price hikes associated with the increased demand for lithium secondary batteries.
[0003] Research and development is being conducted on new positive electrode active materials for secondary batteries to replace lithium secondary batteries, and sulfur-based positive electrode active materials are being researched and developed as one of the candidates. For example, Patent Document 1 discloses that sulfur-modified polyacrylonitrile obtained by heating sulfur powder and polyacrylonitrile powder in a non-oxidizing atmosphere is used as a positive electrode active material for lithium secondary batteries. Patent Document 2 discloses that fluorine-introduced sulfur-modified polyacrylonitrile, which has a higher potential due to the introduction of fluorine, is used as a positive electrode active material for secondary batteries.
[0004] Meanwhile, a method for producing a positive electrode active material using rubbers containing sulfur, such as rubbers derived from tires, as a raw material has been reported (Patent Document 3). In this production method, rubbers are thermally decomposed to separate them into solids and dry distillation gas, the dry distillation gas is cooled to separate them into oil and gas, the oil is distilled and separated, and the sulfur and heavy oil obtained are kneaded and heat-treated to produce a product that is used as the positive electrode active material for lithium secondary batteries.
[0005] Furthermore, Patent Document 4 discloses a method for purifying a carbonized material made from rubber waste, in which a carbonized material obtained by a thermal recycling process of rubber waste is mixed with sodium bicarbonate, then deionized water having an elevated temperature and a strong mineral acid and / or a mineral acid mixture are introduced into the obtained mixture, and then the whole is stirred at an elevated temperature and vacuum filtered while washing with deionized water having an elevated temperature, the filtrate is discarded, a strong base solution is introduced into the solid residue, and the whole is stirred at an elevated temperature, then the obtained suspension is vacuum filtered and washed with deionized water having an elevated temperature, then the filtrate is discarded, and the solid residue is dried. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5534227 [Patent Document 2] JP 2013-101811 A [Patent Document 3] Patent No. 6266655 [Patent Document 4] Special Publication No. 2021-521323 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, secondary batteries using alkali metals other than lithium (Na, K) and alkaline earth metals (Ca, Mg) have also been developed, but lithium secondary batteries are expected to continue to lead the way for portable device and automotive applications that require high volumetric capacity. On the other hand, in the case of stationary secondary batteries, which do not require a high volumetric capacity, i.e., do not need to be compact, the use of secondary batteries of ions other than lithium is envisaged.
[0008] The sulfur-modified polyacrylonitrile-based positive electrode active materials of Patent Documents 1 and 2 are essentially for lithium secondary batteries, and although they have been used in some sodium secondary batteries, the capacity is limited, and they have not been used in secondary batteries using other alkali metals (K) or alkaline earth metals (Ca, Mg). In addition, since a special acrylonitrile is used as a raw material, it is difficult to obtain the raw material, and the cost is likely to be high. In addition, the positive electrode active material using the rubber-derived raw material described in Patent Document 3 has the advantage that waste materials such as rubbers derived from waste tires can be used as the sulfur-containing raw material rubbers. Although it showed excellent performance as a lithium secondary battery, it could not be directly used in secondary batteries of ions other than Li.
[0009] In addition, the method of refining carbonized material using rubber waste as a raw material described in Patent Document 4 required multiple complex processes for the refining treatment, and had technical issues such as the production of waste liquid derived from strong mineral acids and strong base solutions.
[0010] Under these circumstances, an object of the present invention is to provide a method and system for producing an electrode member using a sulfur-containing rubber as a raw material. Another object of the present invention is to provide a novel method for producing a positive electrode active material, a positive electrode active material, a positive electrode mixture, and a secondary battery, using an ion species other than lithium.
[0011] Another object of the present invention is to provide a method for producing a refined carbide using a sulfur-containing rubber as a raw material, the refined carbide obtained by this production method, and a negative electrode mixture and a secondary battery using the refined carbide. Another object of the present invention is to provide a method for producing sulfur using sulfur-containing rubber as a raw material, and a method for producing heavy oil and / or light oil. Another object of the present invention is to provide a method for treating rubbers containing sulfur. [Means for solving the problem]
[0012] As a result of intensive research aimed at solving the above problems, the present inventors discovered that the following invention meets the above object, and thus completed the present invention.
[0013] That is, the present invention relates to the following method for producing an electrode member. <1> A method for producing an electrode member using a sulfur-containing rubber as a raw material, the electrode member being a positive electrode active material, the method comprising the steps of: (1) pyrolyzing the raw material to separate it into a solid and a dry distillation gas; (2) separating an unrefined carbonized material from the solid; (3) washing the unrefined carbonized material and then heat-treating it in a non-oxidizing atmosphere to obtain a refined carbonized material; (4) cooling the dry distillation gas to separate it into an oil and a gas, and distilling the oil into a heavy oil, a light oil, and sulfur; and (5) kneading an ion raw material (A) containing one or more elements selected from the group consisting of Na, K, Ca, and Mg, a carbonized material for a positive electrode active material (B), heavy oil (C), and sulfur (D), and heat-treating the solid obtained in the non-oxidizing atmosphere, and pulverizing and drying the solid obtained to obtain a positive electrode active material, the method for producing an electrode member satisfying any one or more of the following requirements (i) to (iii): Requirement (i): At least a part of the carbonized material (B) for a positive electrode active material is a refined carbonized material obtained by step (3). Requirement (ii): At least a part of the heavy oil (C) is a heavy oil obtained by step (4). Requirement (iii): At least a part of the sulfur (D) is sulfur obtained by step (4). <2> At least a part of the component (A) is one or more selected from the group consisting of inorganic detergents, plant combustion ash, burned eggshells, burned shells, gypsum, and hot spring scale. <1> A method for producing the electrode member according to claim 1. <3> At least a part of component (A) is wood combustion ash obtained by burning wood. <1> or <2> A method for producing the electrode member according to claim 1. <4> At least a part of the component (A) is a baked eggshell product. <1> or <2> A method for producing the electrode member according to claim 1. <5> The washing of the raw carbonized material in step (3) is a subcritical or supercritical process. <1> from <4> 13. A method for producing an electrode member according to any one of claims 1 to 12. <6> The sulfur-containing rubber is rubber derived from tires. <1> or <5> 13. A method for producing an electrode member according to any one of claims 1 to 12. <7> A method for producing an electrode member using a sulfur-containing rubber as a raw material, comprising the steps of: The electrode member is a positive electrode active material, The method for manufacturing an electrode member includes the steps of: pyrolyzing the raw material to separate it into a solid and a dry distillation gas; cooling the dry distillation gas to separate it into an oil and a gas; distilling the oil to separate it into heavy oil, light oil, and sulfur; kneading the heavy oil, sulfur, and an ion raw material containing one or more elements selected from the group consisting of Na, K, Ca, and Mg with a carbide for a positive electrode active material; and heat treating the mixture in a non-oxidizing atmosphere to obtain a positive electrode active material. <8> The ion source is at least one selected from the group consisting of inorganic detergents, plant combustion ash, burned eggshells, burned shells, gypsum, and hot spring scale. <7> A method for producing the electrode member according to claim 1. <9> A manufacturing method for an electrode member using a sulfur-containing rubber as a raw material, the electrode member being a negative electrode active material, the manufacturing method for an electrode member comprising the steps of: pyrolyzing the raw material to separate it into a solid and a dry distillation gas; selecting an unrefined carbonized material from the solid; subjecting the unrefined carbonized material to subcritical or supercritical treatment; and then heat treating the unrefined carbonized material in a non-oxidizing atmosphere to obtain a refined carbonized material as the negative electrode active material. <10> The sulfur-containing rubber is rubber derived from tires. <1> from <9> 13. A method for producing an electrode member according to any one of claims 1 to 12. <11> <1> from <8> Either <10> A positive electrode mixture comprising a positive electrode active material obtained by the manufacturing method described in 1. <12> A battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode is <11> A secondary battery using the positive electrode mixture described in claim 1. <13> The negative electrode is <9> The negative electrode active material obtained by the method of <12> The secondary battery according to claim 1. <14> The electrolyte is tris(2,2,2-trifluoroethyl)phosphate (TFEP) with sodium bis(fluorosulfonyl)imide (NaFSI) or potassium bis(fluorosulfonyl)imide (KFSI) dissolved therein as an electrolyte salt. <12> or <13> The secondary battery according to claim 1.
[0014] The present invention also relates to the following inventions. <1A> A method for producing a refined charcoal using sulfur-containing rubbers as a raw material, the method comprising: a step (1) of pyrolyzing the raw material and separating it into a solid and a dry distillation gas; a step (2) of separating an unrefined charcoal from the solid; and a step (3) of subjecting the unrefined charcoal to subcritical or supercritical treatment, followed by heat treatment in a non-oxidizing atmosphere, to obtain a refined charcoal. <2A> The method for producing a positive electrode active material according to <1A>, wherein the sulfur-containing rubber is a rubber derived from a tire. <3A> The method for producing a refined carbonized product according to <2A>, wherein the rubbers derived from tires are tire dust. <4A> The method for producing a purified charcoal according to any one of <1A> to <3A>, wherein the supercritical fluid used in the subcritical or supercritical treatment in the step (3) is carbon dioxide. <5A> The method for producing a purified charcoal according to any one of <1A> to <4A>, wherein the supercritical fluid used in the subcritical or supercritical treatment in the step (3) is a mixture of carbon dioxide and an alcohol having 3 or less carbon atoms. <6A> The method for producing a purified charcoal according to <5A>, wherein the alcohol having 3 or less carbon atoms is isopropanol. <7A> The method for producing refined carbide according to any one of <1A> to <6A>, wherein the temperature of the heat treatment in a non-oxidizing atmosphere in the step (3) is 650° C. or higher and 1000° C. or lower. <8A> The method for producing a refined carbide according to any one of <1A> to <7A>, comprising the step of pulverizing and sieving the refined carbide after the heat treatment in a non-oxidizing atmosphere in the step (3).
[0015] <9A> A refined carbide obtained by the production method according to any one of <1A> to <8A>. <10A> The refined carbide according to <9A>, having a particle size range of 5 μm or more and 60 μm or less. <11A> A negative electrode mixture containing the refined carbide according to <9A> or <10A> as a negative electrode active material. <12A> A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, the negative electrode being formed using the negative electrode mixture according to <11A>. <13A> The secondary battery according to <12A>, wherein the electrolyte is a phosphate having sodium bis(fluorosulfonyl)imide (NaFSI) or potassium bis(fluorosulfonyl)imide (KFSI) dissolved therein as an electrolyte salt. <14A> The secondary battery according to <13A>, wherein the phosphate is tris(2,2,2-trifluoroethyl)phosphate (TFEP).
[0016] <1B> A method for producing sulfur using sulfur-containing rubbers as a raw material, the method comprising: a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas; and a step (4) of cooling the dry distillation gas to separate it into an oil component and a gas, and distilling the oil component to separate it into a heavy oil, a light oil, and sulfur. <2B> A method for producing heavy oil and / or light oil using sulfur-containing rubbers as a raw material, comprising: a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas; and a step (4) of cooling the dry distillation gas to separate it into an oil fraction and a gas, and distilling the oil fraction to separate it into a heavy oil, a light oil, and sulfur. <3B> The manufacturing method according to <1B> or <2B>, wherein the sulfur-containing rubbers are rubbers derived from tires.
[0017] <1C> A method for treating rubbers containing sulfur, comprising the steps of: The method includes the steps of: (1) pyrolyzing the sulfur-containing rubbers and separating them into a solid material and a carbonization gas; (2) separating an unrefined carbonized product from the solid material; and (3) washing the unrefined carbonized product and then heat-treating it in a non-oxidizing atmosphere to obtain a refined carbonized product. A method for treating sulfur-containing rubbers comprising the steps of: <2C> The method for treating sulfur-containing rubbers according to <1C>, wherein the sulfur-containing rubbers are rubbers derived from tires.
[0018] The present invention also relates to the following manufacturing system for an electrode member. <1a> <1> from <10> A production system for any one of the methods for producing an electrode member according to any one of <1A> to <8A>, the method for producing refined carbide according to any one of <1B> to <3B>, or the method for producing heavy oil and / or light oil, The present invention relates to a heat treatment means (x) for pyrolyzing the raw material and separating it into a solid material and a carbonization gas, a separation means (y1) for separating an unrefined carbonized material from the solid material, a washing means (y2) for washing the unrefined carbonized material, a heat treatment means (y3) for heat treating the washed unrefined carbonized material in a non-oxidizing atmosphere to obtain a refined carbonized material, and a separation means (z) for cooling the carbonization gas to separate it into an oil component and a gas, and for distilling the oil component to separate it into a heavy oil, a light oil, and sulfur. a kneading means (z2) for kneading an ion raw material (A) containing one or more elements selected from the group consisting of Na, K, Ca, and Mg, a carbonized material for a positive electrode active material (B), heavy oil (C), and sulfur (D) to obtain a raw material mixture, a heat treatment means (z3) for heat treating the raw material mixture in a non-oxidizing atmosphere to obtain a solid matter, and an adjustment means (z4) for pulverizing and drying the obtained solid matter. <2a> The system for manufacturing an electrode member according to <1a>, wherein the unrefined carbonized material is subjected to subcritical or supercritical treatment in a cleaning means (y2). <3a> The electrode member manufacturing system described in <2a>, wherein the electrode member manufacturing system has a gas processing means (w1) that combusts the gas separated by the separation means (z1) and recovers the generated carbon dioxide, and in a cleaning means (y2), the unrefined carbonized material is subjected to subcritical or supercritical treatment using the carbon dioxide recovered by the gas processing means (w1). <4a> The system for manufacturing an electrode member according to any one of <1a> to <3a>, wherein the heat treatment means (x) combusts the light oil separated by the separation means (z1) and uses the generated heat to pyrolyze the raw material. <5a> The system for producing an electrode member according to any one of <1a> to <4a>, comprising a crushing means (w3) for crushing the refined carbide obtained by the heat treatment means (y3). <6a> The system for producing an electrode member according to any one of <1a> to <5a>, comprising an ion raw material producing means (w4) for producing one or more substances selected from the group consisting of inorganic detergents, plant combustion ash, burned eggshells, burned seashells, gypsum and hot spring scale. <7a> The electrode member manufacturing system according to any one of <1a> to <6a>, further comprising a neutralization means (w5), which produces the neutralized solid content by neutralizing the sulfide generated in the heat treatment means (z3), and the ion raw material (A) contains the neutralized solid content. <8a> The system for producing an electrode member according to any one of <1a> to <7a>, wherein the sulfur-containing rubber is a rubber derived from tires. Effect of the Invention
[0019] According to the present invention, there are provided a method and a system for manufacturing an electrode member using a sulfur-containing rubber as a raw material, a method for manufacturing a positive electrode active material containing an ion species other than lithium, a positive electrode active material, a positive electrode mixture, and a secondary battery.
[0020] The present invention also provides a method for producing a purified carbide using a sulfur-containing rubber as a raw material, and the purified carbide obtained by the production method. Also provided are a negative electrode mixture and a secondary battery using the purified carbide. The present invention also provides a method for producing sulfur using sulfur-containing rubber as a raw material, and a method for producing heavy oil and / or light oil. [Brief description of the drawings]
[0021] [Figure 1] 1 is a conceptual diagram of a manufacturing system for an electrode member according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention. In this specification, the word "~" is used as an expression including the numerical value or physical quantity before and after it. In this specification, the expression "A and / or B" includes "A only," "B only," and "both A and B."
[0023] (Definition of terms) In this specification, the term "electrode member" means "members constituting the electrodes of a battery", and specifically means electrode active materials (positive electrode active materials and negative electrode active materials), conductive materials (positive electrode conductive materials and negative electrode conductive materials), and current collectors (positive electrode current collectors and negative electrode current collectors). In this specification, the term "positive electrode active material" refers to an electrode active material that is used for a positive electrode among materials involved in a reaction that generates electric energy, and the term "negative electrode active material" refers to an electrode active material that is used for a negative electrode among materials involved in a reaction that generates electric energy.
[0024] In addition, in this specification, the term "carbonized product" is a concept that encompasses not only "a carbon material consisting of pure carbon atoms" but also "a material containing carbon atoms and impurities (such as mineral components derived from carbon-containing raw materials) obtained by heat treating a carbon-containing raw material." In addition, in this specification, the term "unrefined carbonized material" refers to a carbonized material separated from a solid material obtained by pyrolysis of a raw material that is a sulfur-containing rubber. In addition, in this specification, a "purified carbide" refers to a carbide obtained after washing an unpurified carbide, and in particular, a carbide obtained by subjecting the carbide to a subcritical or supercritical washing treatment followed by a heat treatment in a non-acidic atmosphere is referred to as the "purified carbide of the present invention."
[0025] In addition, in this specification, "subcritical or supercritical treatment" refers to a treatment for cleaning an object by contacting the object with a treatment fluid (supercritical fluid) in a subcritical or supercritical state.
[0026] <1-1. Method for producing positive electrode active material> The present invention relates to a method for producing a positive electrode active material, comprising a step of heat-treating a raw material mixture obtained by mixing the following components (A) to (D) in a non-oxidizing atmosphere (hereinafter referred to as the "method for producing the positive electrode active material of the present invention"). Component (A): An ion source containing one or more elements selected from the group consisting of Na, K, Ca, and Mg. Component (B): Carbide for positive electrode active material Component (C): Heavy oil Component (D): Sulfur
[0027] The positive electrode active material of the present invention can be produced as follows using the components (A) to (D) as starting materials, that is, by carrying out the following steps (p1) and (p2) in this order. Step (p1): A step of mixing components (A) to (D) to obtain a raw material mixture. Step (p2): A step of heat-treating the obtained raw material mixture in a non-oxidizing atmosphere to obtain a heat-treated product.
[0028] The positive electrode active material of the present invention can be suitably manufactured by the "electrode member manufacturing system of the present invention" described later in <2. Electrode member manufacturing method and electrode member manufacturing system>, but is not limited thereto, and the positive electrode active material manufacturing method of the present invention can also be performed using manufacturing equipment other than the "electrode member manufacturing system of the present invention".
[0029] The method for producing the positive electrode active material of the present invention will be described in detail below.
[0030] <Process (p1)> The step (p1) is a step of mixing the components (A) to (D) to obtain a raw material mixture.
[0031] <Component (A)> Component (A) is an ion source containing one or more elements selected from the group consisting of Na, K, Ca, and Mg.
[0032] The ionic raw material, which is component (A), refers to a raw material that contains the target ionic species (Na, K, Ca, or Mg) and can provide the desired ionic species to the positive electrode active material.
[0033] The ion source as component (A) may be one type, or two or more types may be used. When two or more types of ion sources are used, the ion species may be the same or different.
[0034] Examples of the component (A) include percarbonates, carbonates, hydrogen carbonates, sulfates, and nitrates of Na, K, Ca, or Mg. As component (A), new raw materials can be used, but it is preferable to use raw materials derived from waste materials. As component (A), only new raw materials may be used, only raw materials derived from waste materials may be used, or new raw materials and raw materials derived from waste materials may be mixed (mixed in any ratio).
[0035] One suitable example of component (A) is an inorganic detergent containing a peroxygen bleach. The sodium percarbonate contained in the peroxygen bleach of the inorganic detergent can be a suitable sodium source.
[0036] One suitable example of component (A) is plant combustion ash (particularly wood combustion ash). "Plant fuel ash" is the combustion ash of a plant-based raw material, and contains Na, K, Ca, and Mg (particularly Ca) derived from the plant-based raw material, as well as other mineral components. There are no particular limitations on the plant-based raw material as long as it does not impair the object of the present invention, but from the viewpoint of waste utilization, it is preferable that the plant-based raw material is at least one selected from rice husks, straw, bamboo, thinning materials, and weeds. One suitable example of plant combustion ash is wood combustion ash, which is the combustion ash of wood raw material. The wood raw material is not particularly limited as long as it does not impair the object of the present invention, but typically includes broad-leaved trees such as cedar, larch, and cypress, coniferous trees such as beech, birch, and oak, and bamboo. In addition, from the viewpoint of waste utilization, examples of wood raw materials include wood from dismantled houses, wood waste from sawmills, wood waste from furniture factories, and wood from trees.
[0037] One suitable example of component (A) is a calcined biological material containing calcium. Examples of "calcium-containing biological materials" include eggshells and seashells, and calcined eggshells and seashells can be suitably used as ion sources that provide calcium.
[0038] One suitable example of component (A) is gypsum. "Gypsum" is a mineral containing calcium sulfate and is suitable as a calcium source. The gypsum is not particularly limited as long as it does not impair the object of the present invention, but from the viewpoint of waste utilization, gypsum produced by separating gypsum boards can be used.
[0039] One suitable example of component (A) is hot spring scale. "Hot spring scale" is a deposit of components that were originally dissolved in hot spring water but have since precipitated as insoluble components due to changes in temperature or pressure, contact with air, or contact with pipes, etc. The components of hot spring scale depend on the original hot spring water, but include at least one of calcium, sodium, potassium, and magnesium. Hot spring scale often also contains components such as silica-based minerals and iron oxide hydroxide, so these may be removed as necessary before use as component (A).
[0040] <Ingredient (B)> The carbonized product for a positive electrode active material, which is component (B), is a carbonized product used as a raw material for a positive electrode active material. As the carbonized material for the positive electrode active material, any carbon material can be used as long as it does not impair the object of the present invention. Examples of the carbonized material include graphite powder, carbon black (e.g., acetylene black, ketjen black, furnace black, etc.), and fibrous carbon materials (carbon nanotubes, carbon nanofibers, vapor-grown carbon fibers, etc.).
[0041] In addition, the carbonized material for the positive electrode active material is preferably a carbon-containing raw material that is heat-treated under inactive conditions. The carbonized raw material for the carbonized material may be any raw material as long as it does not impair the object of the present invention, and may include biomass raw materials (e.g., wood, bamboo, rice husk, etc.), various resin materials, and plastics such as rubber materials. These carbonized raw materials may be used alone or in combination of two or more.
[0042] It is preferable that component (B) contains at least a portion of a refined carbide which will be described later in <2. Manufacturing method and manufacturing system for electrode member>. That is, a suitable example of the carbonized material for positive electrode active material, which is component (B), is a refined carbonized material obtained by pyrolyzing a rubber containing sulfur to separate it into a solid and a dry distillation gas, separating the carbonized material from the solid, and heat-treating the unrefined carbonized material.
[0043] The heat treatment conditions are appropriately determined in consideration of the type of carbon-containing raw material and the physical properties (crystallinity, porosity, etc.) of the target carbonized product. Typically, the carbon-containing raw material is heated in a non-oxidizing atmosphere (e.g., under a flow of an inert gas such as N2) to perform the carbonization treatment. The carbonization temperature is, for example, 500°C or higher and 1200°C or lower.
[0044] <Ingredient (C)> The heavy oil as component (C) is an essential component of the positive electrode active material, and also functions as a binder that binds the other components together during production.
[0045] As the heavy oil, any of coal tar-based, petroleum-based and rubber-based oils can be used.
[0046] Component (C) preferably contains at least a portion of heavy oil, which will be described later in <2. Manufacturing method of electrode member and manufacturing system of electrode member>. That is, a suitable example of the heavy oil which is component (C) is a heavy oil at least a portion of which is obtained by thermally decomposing sulfur-containing rubbers to separate them into solids and dry distillation gas, cooling the dry distillation gas to separate it into an oil fraction and a gas, and distilling the oil fraction to separate it into heavy oil, light oil, and sulfur.
[0047] <Ingredient (D)> The sulfur as component (D) may be a commercially available product, or may be one separated from a compound or composition containing sulfur.
[0048] Component (D) preferably contains at least a portion of sulfur, which will be described in <2. Manufacturing method of electrode member and manufacturing system of electrode member> below. That is, at least a portion of component (D) is sulfur obtained by thermally decomposing sulfur-containing rubbers to separate them into solids and carbonization gas, cooling the carbonization gas to separate it into an oil component and gas, and distilling the oil component to separate it into heavy oil, light oil, and sulfur.
[0049] In a preferred example of the method for producing a positive electrode active material of the present invention, component (A) is one or more selected from the group consisting of inorganic detergents, plant combustion ash, burned eggshells, burned seashells, gypsum, and hot spring scale, at least a portion of component (B) is a refined carbonized material obtained by thermally decomposing sulfur-containing rubbers to separate them into a solid matter and a dry distillation gas, selecting an unrefined carbonized material from the solid matter, and heat treating the unrefined carbonized material, at least a portion of component (C) is a heavy oil obtained by cooling the dry distillation gas to separate it into an oil matter and a gas, and distilling the oil matter to separate it into a heavy oil matter, a light oil matter, and sulfur, and at least a portion of component (D) is sulfur obtained by distilling the oil matter to separate it into a heavy oil matter, a light oil matter, and sulfur.
[0050] The proportions of the components (A) to (D) are appropriately determined depending on the types of the components (A) to (D) within the range in which they function as a positive electrode active material. For example, when component (A) is wood combustion ash, suitable ratios of components (A) to (D) are 20 to 60 weight % of component (A), 10 to 30 weight % of component (B), 5 to 15 weight % of component (C), and 20 to 40 weight % of component (D).
[0051] In step (p1), the mixing method may be dry mixing, which is generally used in the industry. Examples of dry mixing devices include a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, and a dry ball mill. Mixing may also be performed by wet mixing, provided that the object of the present invention is not impaired.
[0052] <Process (p2)> Step (p2) is a step of heat-treating the raw material mixture obtained in step (p1) in a non-oxidizing atmosphere to obtain a heat-treated product. The heat-treated product (positive electrode active material) is obtained by step (p2).
[0053] In this specification, the term "non-oxidizing atmosphere" refers to an atmosphere that does not substantially contain an oxidizing gas such as oxygen, and is typically an inert gas atmosphere such as nitrogen, argon, helium, etc. Furthermore, as long as it does not impair the object of the present invention, a reducing atmosphere such as hydrogen or an inert gas containing hydrogen may also be used.
[0054] In the step (p2), the heat treatment of the raw material mixture is carried out, for example, by placing the raw material mixture in a non-oxidizing atmosphere, raising the temperature from room temperature to a heat treatment temperature, carrying out the heat treatment at the heat treatment temperature for a predetermined time, and then lowering the temperature to, for example, room temperature.
[0055] The heat treatment temperature and heat treatment time are appropriately set according to the types and proportions of the components (A) to (D) within the range in which the desired heat-treated product (positive electrode active material) is produced. The heat treatment temperature is, for example, 250° C. or more and 500° C. or less (preferably 300° C. or more and 400° C. or less). The heat treatment time is, for example, 10 minutes or more and 10 hours or less.
[0056] The heat-treated product obtained in step (p2) is used after being pulverized as necessary. The pulverization method may be an industrially commonly used pulverization method. Examples of the pulverization device include pulverizers such as vibration mills, jet mills, and dry ball mills. In addition, a classification operation such as air classification may be performed as necessary.
[0057] A preferred example of the method for producing a positive electrode active material of the present invention is a method for producing an electrode member using a sulfur-containing rubber as a raw material, the method comprising: a step (1) of pyrolyzing the raw material to separate it into a solid and a dry distillation gas; a step (2) of separating an unrefined carbonized material from the solid; a step (3) of washing the unrefined carbonized material and then heat-treating it under a non-oxidizing atmosphere to obtain a refined carbonized material; a step (4) of cooling the dry distillation gas to separate it into an oil and a gas, and distilling the oil to separate it into a heavy oil, a light oil, and sulfur; and a step (5) of kneading an ion raw material (A) containing one or more elements selected from the group consisting of Na, K, Ca, and Mg, a carbonized material for a positive electrode active material (B), heavy oil (C), and sulfur (D), and heat-treating the solid obtained under a non-oxidizing atmosphere, pulverizing the solid obtained, and drying the kneaded solid obtained, and the method is characterized in that the method satisfies any one or more of the following requirements (i) to (iii). Requirement (i): At least a part of the carbonized material (B) for a positive electrode active material is a refined carbonized material obtained by step (3). Requirement (ii): At least a part of the heavy oil (C) is a heavy oil obtained by step (4). Requirement (iii): At least a part of the sulfur (D) is sulfur obtained by step (4).
[0058] A suitable example of the method for producing a positive electrode active material of the present invention preferably contains at least a portion of refined carbide, heavy oil and sulfur, which will be described later in <2. Method for producing electrode member and system for producing electrode member>.
[0059] <1-2. Manufacturing method of refined carbide> The method for producing refined carbonized material of the present invention is a method for producing refined carbonized material using sulfur-containing rubbers as a raw material, and is characterized by comprising the steps of pyrolyzing the raw material to separate it into a solid material and a dry distillation gas, separating an unrefined carbonized material from the solid material, subjecting the unrefined carbonized material to subcritical or supercritical treatment, and then heat treating it in a non-oxidizing atmosphere to obtain a refined carbonized material.
[0060] The method for producing refined carbonized material of the present invention is a method for producing refined carbonized material using sulfur-containing rubbers as a raw material, and includes the steps of (1) pyrolyzing the raw material and separating it into a solid and a dry distillation gas, (2) separating an unrefined carbonized material from the solid, and (3) subjecting the unrefined carbonized material to subcritical or supercritical treatment and then heat treating it in a non-oxidizing atmosphere to obtain a refined carbonized material.
[0061] The method for producing the refined carbide of the present invention can be suitably carried out by the "system for producing an electrode member of the present invention" described in <2. Method for producing an electrode member and system for producing an electrode member> below. A specific description of the method for producing the refined carbide of the present invention will be given together with the "system for producing an electrode member of the present invention". The method for producing refined carbide of the present invention can also be carried out using production equipment other than the "electrode member production system of the present invention" as long as it satisfies the object of the present invention.
[0062] The refined carbide of the present invention can be suitably used as a carbide for a positive electrode active material (the above component (B)) which is an electrode member for a secondary battery, or as a negative electrode active material, but can also be used for other purposes.
[0063] When used as a negative electrode active material, it is preferable to use a refined carbide that has been subjected to heat treatment in a non-oxidizing atmosphere at 650° C. or higher and 1000° C. or lower in the step (3).
[0064] When used as a negative electrode active material, it is preferable to use a purified carbide in which the particle size range is controlled by crushing and sieving the purified carbide after the heat treatment under a non-oxidizing atmosphere in step (3). The particle size range when used as a negative electrode active material is preferably 5 to 60 μm, more preferably 10 to 30 μm.
[0065] <1-3. Sulfur manufacturing method> The method for producing sulfur of the present invention is a method for producing sulfur using sulfur-containing rubbers as a raw material, and includes a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas, and a step (4) of cooling the dry distillation gas to separate it into an oil component and a gas, and distilling the oil component to separate it into heavy oil, light oil, and sulfur.
[0066] The method for producing sulfur of the present invention can be suitably carried out by the "system for producing an electrode member of the present invention" described in <2. Method for producing an electrode member and system for producing an electrode member> below. The specific method for producing sulfur of the present invention will be described in conjunction with the "system for producing an electrode member of the present invention". The method for producing sulfur of the present invention can be carried out using production equipment other than the "electrode member production system of the present invention" as long as it satisfies the object of the present invention.
[0067] The produced sulfur can be suitably used as sulfur for a positive electrode active material (the above component (D)), which is an electrode member for a secondary battery, but can also be used for other purposes.
[0068] <1-4. Manufacturing method of heavy oil and / or light oil> The method for producing heavy oil and / or light oil of the present invention is a method for producing heavy oil and / or light oil using sulfur-containing rubbers as a raw material, and includes a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas, and a step (4) of cooling the dry distillation gas to separate it into an oil fraction and a gas, and distilling the oil fraction to separate it into heavy oil, light oil, and sulfur.
[0069] The method for producing heavy oil and / or light oil of the present invention can be suitably carried out by the "system for producing an electrode member of the present invention" described in <2. Method for producing an electrode member and system for producing an electrode member> below. A specific description of the method for producing heavy oil and / or light oil of the present invention will be given together with the "system for producing an electrode member of the present invention". The method for producing heavy oil and / or light oil of the present invention can also be carried out using production equipment other than the "electrode member production system of the present invention" as long as it satisfies the object of the present invention.
[0070] The heavy oil and / or light oil produced may be used for any purpose. In particular, the heavy oil produced may be suitably used as heavy oil (component (C)) for a positive electrode active material, which is an electrode member of a secondary battery, but may also be used for other purposes.
[0071] <2. Manufacturing method and manufacturing system for electrode member> The above-mentioned <1-1. Manufacturing method of positive electrode active material>, <1-2. Manufacturing method of refined carbon>, <1-3. Manufacturing method of sulfur> and <1-4. Manufacturing method of heavy oil and / or light oil> can be part of a manufacturing method of an electrode member using a sulfur-containing rubber as a raw material described below (hereinafter referred to as "the manufacturing method of the electrode member of the present invention"). In the following description, the "method for producing a positive electrode active material," the "method for producing a refined carbide," the "method for producing sulfur," and the "method for producing heavy oil and / or light oil" will be collectively referred to as the "method for producing an electrode member of the present invention" for convenience. However, there is no intention to restrict the use of the products obtained by the "method for producing a refined carbide," the "method for producing sulfur," and the "method for producing heavy oil and / or light oil" for purposes other than electrode members, and they can be used for electrode members and other purposes.
[0072] In addition, the manufacturing method for the electrode member of the present invention can be suitably realized using a manufacturing system for the electrode member described below (hereinafter referred to as the "manufacturing system for the electrode member of the present invention"). However, as long as any one of the "manufacturing method for the positive electrode active material", "manufacturing method for the refined carbide", "manufacturing method for the sulfur", and "manufacturing method for the heavy oil and / or light oil" can be realized, manufacturing systems or processing systems other than the manufacturing system for the electrode member of the present invention can also be used.
[0073] In the method for producing an electrode member of the present invention, when producing an electrode member (electrode active material, conductive material, and current collector) from sulfur-containing rubbers as raw materials, not only the carbide, sulfur, and heavy oil that are the main raw materials for the electrode member, but also the light oil, sulfide, carbon dioxide, and exhaust heat that are generated as by-products can be reused and used as raw materials or energy. Therefore, the method for producing an electrode member of the present invention can use sulfur-containing rubbers such as tires as raw materials for battery members.
[0074] The method for producing an electrode member of the present invention can use new raw materials, but has the advantage of being able to effectively use rubbers (e.g., waste tires, etc.) and tire dust that are usually discarded as raw materials. In this specification, "tire dust" refers to fine particles generated by repeated contact friction between vehicle tires and the road surface.
[0075] The above-mentioned method for producing an electrode member of the present invention can be suitably carried out by using the system for producing an electrode member of the present invention.
[0076] The electrode member manufacturing system of the present invention is a manufacturing system for an electrode member using the above-mentioned manufacturing method for an electrode member of the present invention, and includes a heat treatment means (x) for pyrolyzing the raw material and separating it into a solid and a dry distillation gas, a separation means (y1) for separating an unrefined carbide from the solid, a washing means (y2) for washing the unrefined carbide, a heat treatment means (y3) for heat treating the washed unrefined carbide in a non-oxidizing atmosphere to obtain a refined carbide, and a cooling means (y4) for cooling the dry distillation gas to separate it into an oil component and a gas, and a heat treatment means (y5) for cooling the dry distillation gas to separate it into an oil component and a gas, and a heat treatment means (y6) for cooling the dry distillation gas to obtain a refined carbide. The system for manufacturing an electrode member includes a separation means (z1) for separating the oil into heavy oil, light oil, and sulfur by distillation, a kneading means (z2) for kneading an ion raw material (A) containing one or more elements selected from the group consisting of Na, K, Ca, and Mg, a carbonized material for a positive electrode active material (B), heavy oil (C), and sulfur (D) to obtain a raw material mixture, a heat treatment means (z3) for heat-treating the raw material mixture in a non-oxidizing atmosphere to obtain a solid material, and an adjustment means (z4) for pulverizing and drying the obtained solid material.
[0077] An example of an embodiment of the electrode member manufacturing method and the electrode member manufacturing system of the present invention will be described below with reference to the drawings. Note that the present invention is not limited to the following embodiment, and can be modified and carried out as desired without departing from the gist of the present invention.
[0078] FIG. 1 is a conceptual diagram of a manufacturing system for battery components according to an embodiment of the present invention. As shown in FIG. 1, in the battery component manufacturing system of this embodiment, sulfur-containing rubbers are used as raw materials, the raw materials are thermally decomposed to separate them into solids and dry distillation gas, unrefined carbonized material is selected from the solids, refined carbonized material (carbonized material for negative electrode active material and / or positive electrode active material (corresponding to component (B) above)) is produced from the obtained unrefined carbonized material, the dry distillation gas is cooled to separate it into oil and gas components, the oil components are distilled to separate it into heavy oil, light oil, and sulfur, and the obtained heavy oil (corresponding to component (C) above) and sulfur (corresponding to component (D) above), refined carbonized material (corresponding to component (B) above), and ion raw material (corresponding to component (A) above) are kneaded and heat-treated to produce a positive electrode active material. In this way, rubbers containing sulfur as a raw material can be recycled and used as electrode materials.
[0079] The negative electrode active material thus obtained can be applied together with a binder to a negative electrode current collector to produce a negative electrode. The positive electrode active material thus obtained can be applied together with a binder to a positive electrode current collector to produce a positive electrode. The produced positive electrode and negative electrode can be used to produce a battery. The negative electrode active material, the negative electrode conductive material, and the negative electrode, and the positive electrode active material, the positive electrode conductive material, and the positive electrode according to the present invention are not limited to being used to manufacture the same battery, and can also be used to manufacture separate batteries.
[0080] In the battery component manufacturing system according to the embodiment of the present invention, first, rubber as a raw material is thermally decomposed using a thermal decomposition furnace as a heat treatment means (x), whereby the rubber is separated into a solid material and a gaseous dry distillation gas. The heat for pyrolyzing the rubber raw material in the pyrolysis furnace is the combustion heat generated when light oil is burned in the combustion furnace, which is the combustion means (w2). If there is insufficient combustion heat, fuel is added from outside to heat the system. By using the combustion heat from light oil, the need to add fuel from outside is reduced, improving the energy efficiency of the manufacturing method (and manufacturing system) according to this embodiment. The thermal decomposition conditions in the thermal treatment means (x) (shape and dimensions of the thermal decomposition furnace, temperature, thermal decomposition time, etc.) can be appropriately set depending on the amount and type of raw material to be thermally decomposed, etc. Any thermal treatment means can be used as the thermal treatment means (x) as long as it can thermally decompose the raw material and separate it into a solid and a dry distillation gas.
[0081] The raw rubber may be any rubber containing sulfur, and is preferably rubber derived from tires. Here, "rubbers derived from tires" refers to rubbers contained in tires, and tires are obtained by removing components other than rubber (metals such as reinforcing materials). The tire may be any tire that uses vulcanized rubber, and examples of such tires include pneumatic tires, solid tires, etc. In addition, new tires can be used as the raw rubber material, but tires that are discarded after use (scrap tires) and waste materials that are generated and discarded as defective or surplus materials during the tire manufacturing process and contain sulfur-containing rubber as the main component can also be used. Furthermore, the rubbers used as raw materials can be used not only for the above-mentioned tires, but also for, for example, vibration-proof rubber components for automobiles.
[0082] Furthermore, tire dust may be used as rubber derived from tires. Tire dust does not contain iron or other materials other than rubber, and contains essentially only rubber components. Therefore, using tire dust as the raw rubber material has the advantage that it does not require the process of removing components other than rubber contained in the tires (metals such as reinforcing materials) (the sorting process (y1) described below).
[0083] The solid matter separated from the rubbers by pyrolysis is sorted using a sorting machine, which is a sorting means (y1). This separates the solid matter into crude charcoal and matter other than crude charcoal (typically metals). As described above, tires contain metals such as reinforcing materials in addition to rubbers, and the sorting process removes the metals from the solid matter.
[0084] The sorting means (y1) may be any sorting means capable of sorting out the crude carbide from the solid material obtained by the heat treatment means (x). For example, a magnetic separator, a wind separator, or a sieve separator may be used as the sorting means (y1).
[0085] The metals separated from the solids can be recycled as metal resources.
[0086] On the other hand, the unrefined charcoal separated from the solid matter is washed to remove impurities. Specifically, the unrefined charcoal is washed by subcritical or supercritical treatment using a subcritical / supercritical treatment device, which is the washing means (y2), and the quality and performance of the unrefined charcoal can be improved. The unrefined char separated from the solids may be crushed, if necessary, before washing.
[0087] Subcritical or supercritical processing is a process for cleaning unrefined charcoal by contacting the unrefined charcoal to be processed with a processing fluid (supercritical fluid) in a subcritical or supercritical state.
[0088] The supercritical fluid used in the subcritical or supercritical treatment may be a substance that is a gas or liquid at room temperature and pressure, and that is in a subcritical or supercritical state at a temperature of 80 to 400° C. and a pressure of 5 to 50 MPa.
[0089] As the supercritical fluid, for example, carbon dioxide, saturated or unsaturated lower hydrocarbons having 3 or less carbon atoms, such as methane, ethane, propane, ethylene, and propylene, and lower alcohols having 3 or less carbon atoms, such as methanol, ethanol, n-propanol, and isopropanol, can be used.
[0090] A suitable example of the supercritical fluid is carbon dioxide. In this case, the conditions of the subcritical or supercritical treatment are, for example, a pressure in the treatment device of 7 to 25 MPa, a temperature of 85 to 110° C., and a treatment time of 0.5 to 3 hours.
[0091] A suitable example of the supercritical fluid is a mixture of carbon dioxide and an alcohol having a carbon number of 3 or less. In this case, the conditions of the subcritical or supercritical treatment are, for example, a pressure in the treatment device of 7 to 30 MPa, a temperature of 85 to 300°C, and a treatment time of 0.5 to 3 hours. The ratio of carbon dioxide to alcohol with three or less carbon atoms can be any ratio as long as it reaches a subcritical or supercritical state. As the alcohol having 3 or less carbon atoms used as the supercritical fluid, any of methanol, ethanol, n-propanol, and isopropanol can be used, with isopropanol being a preferred example.
[0092] When a mixture of carbon dioxide and an alcohol having three or less carbon atoms is used as the supercritical fluid, the alcohol having three or less carbon atoms acts as a polar solvent and has the effect of extracting impurities contained in the unrefined carbonized material to be treated, thereby enabling more effective cleaning.
[0093] The inside of the treatment device is maintained in a subcritical or supercritical state, and after the unrefined carbonized material is washed, the inside of the treatment device is returned to normal pressure, and the supercritical fluid that was in a supercritical or subcritical state is returned to a gas or liquid, after which the washed refined carbonized material is recovered. In addition, the carbon dioxide used as the supercritical fluid is recovered and reused as a supercritical fluid. As alcohol with a carbon number of 3 or less contains impurities as a supercritical fluid, it is not reused as a supercritical fluid, but is discarded or used for other purposes (fuel for combustion).
[0094] The resulting refined carbide can be used as a negative electrode active material or a positive electrode active material, or for other applications. The carbide purified by subcritical or supercritical treatment may be used as it is as regenerated carbon black, but may be further subjected to post-treatment (heat treatment, pulverization treatment, etc.). In particular, when the carbide is used as a negative electrode active material or a positive electrode active material, it is preferable to perform heat treatment.
[0095] A refined carbide can be obtained by heat treatment (under a non-oxidizing atmosphere at 500 to 1200°C) using a heat treatment device, which is the heat treatment means (y3). The refined carbide obtained can be recycled and reused as a carbide for a negative electrode active material or a positive electrode active material. The heat treatment conditions (shape and dimensions of the heat treatment machine, temperature, heat treatment time, etc.) in the heat treatment means (y3) can be appropriately set depending on the amount and type of the unrefined carbide to be heat-treated, etc. Any heat treatment means can be used for the heat treatment means (y3) as long as it can heat-treat the unrefined carbide to be heat-treated in a non-oxidizing atmosphere and obtain a refined carbide (a carbonized material for a negative electrode active material and a carbonized material for a positive electrode active material).
[0096] The heat treatment temperature in a non-oxidizing atmosphere is preferably 650° C. to 1000° C., and more preferably 700° C. to 900° C. The heat treatment temperature is, for example, 0.5 hours to 3 hours.
[0097] Furthermore, the resulting refined carbide is preferably subjected to a treatment to remove iron, particularly when used as a negative electrode active material.
[0098] When the obtained refined carbide is used as a negative electrode active material, it is preferable to pulverize it. The obtained refined carbide can be pulverized and pulverized by a pulverizer, which is the pulverizing means (w3). The pulverized refined carbide can be molded with a binder as a negative electrode active material and recycled as a negative electrode of a battery. The pulverizing means (w3) may be a pulverizer such as a vibration mill, a jet mill, or a dry ball mill.
[0099] When used as a negative electrode active material, the finely powdered refined carbide is preferably sieved to adjust the particle size within a certain range. When used as a negative electrode active material, the particle size range is preferably 5 to 60 μm, and more preferably 10 to 30 μm.
[0100] The resulting refined carbide can also be used for purposes other than the negative electrode active material of secondary batteries and conductive materials (for example, active materials for capacitors and carriers for fuel cell catalysts).
[0101] On the other hand, the carbonized gas separated from the rubbers by thermal decomposition is sent to a separation means (z1) for separating the carbonized gas. The separation means (z1) has a cooler for separating the carbonized gas into gas and liquid, a distiller for distilling the liquid separated by the cooler, and a desulfurizer (not shown) for removing sulfur from the gas or liquid. The carbonized gas is first cooled using a cooler, whereby the carbonized gas is separated into a liquid oil fraction and a gas fraction (non-condensed gas).
[0102] Here, the production ratio and composition of heavy oil and non-condensable gas can be controlled by the cooling temperature of the cooler. Lowering the cooling temperature increases the production ratio of heavy oil and decreases the amount of hydrocarbons contained in the non-condensable gas. Therefore, it is possible to detect the hydrocarbon concentration of the non-condensable gas with a detector and control the cooling temperature so that the concentration is constant.
[0103] The non-condensed gas separated from the dry distillation gas is decompressed and then desulfurized using a desulfurizer. The sulfur recovered by the desulfurizer can be used to manufacture a positive electrode active material.
[0104] The non-condensed gas after the desulfurization process is a hydrocarbon gas that does not contain sulfur, and is sent to the gas processing means (w1). The gas processing means (w1) has a combustor and a carbon dioxide recovery device. The condensed gas after the desulfurization process is burned in the combustor, and then the carbon dioxide is recovered in the carbon dioxide recovery device, and the rest is exhausted. A part or all of the recovered CO2 can be used for the subcritical or supercritical treatment of the unrefined char in the above-mentioned washing means (y2).
[0105] When an alcohol with three or fewer carbon atoms is used together with carbon dioxide as a supercritical fluid, the alcohol with three or fewer carbon atoms contains impurities that have been dissolved from the unrefined carbonized material. Therefore, it is not reused as a supercritical fluid, but is discarded or used for other purposes (as a fuel for combustion).
[0106] On the other hand, the oil fraction separated from the dry distillation gas is distilled at a temperature equal to or higher than the boiling point of sulfur using a distiller. This process separates light oil containing a large amount of sulfur, and leaves heavy oil containing almost no sulfur.
[0107] Light oil containing sulfur is desulfurized in a desulfurizer to separate it into sulfur and light oil not containing sulfur, which can then be recovered. The separated light oil not containing sulfur can then be recycled as fuel.
[0108] The separation means (z1) in this embodiment has a cooler, a distiller, and a desulfurizer, but any separation means can be used for the separation means (z1) in the present invention as long as it can separate the dry distillation gas obtained by the heat treatment means (x) into gas components, heavy oil, light oil, and sulfur.
[0109] As described above, the separated heavy oil and sulfur are kneaded together with the refined carbide (positive electrode active material) and ion raw material recovered from the solid matter using a kneader which is the kneading means (z2), and then heat-treated in a heat treatment machine (non-oxidizing atmosphere) which is the heat treatment means (z3). The mixture is then pulverized in a pulverizer included in the adjustment means (z4), and further dried in a vacuum dryer included in the adjustment means (z4), thereby producing the desired solid positive electrode active material.
[0110] The kneading means (z2), the heat treatment means (z3) and the adjusting means (z4) are optional as long as they do not impair the object of the present invention. The kneading means (z2) may be a dry mixer that is commonly used industrially. Examples of the dry mixer include a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, and a dry ball mill. The kneading may also be performed by wet mixing as long as it does not impair the object of the present invention. The heat treatment means (z3) may be an electric heat treatment machine, a combustion heat treatment machine, a batch type heat treatment machine, or a flow type heat treatment machine. Examples of the pulverizer included in the adjusting means (z4) include a vibration mill, a jet mill, and a dry ball mill.
[0111] Here, the ion raw material, the carbonized material for the positive electrode active material, the heavy oil, and the sulfur correspond to the components (A), (B), (C), and (D) in the above-mentioned <1. Method for producing the positive electrode active material>, respectively.
[0112] The ion raw material has been described in detail above as component (A), so a detailed description thereof will be omitted here. For example, raw materials such as inorganic detergents, eggshells, plant-derived raw materials (vegetation), shells, gypsum, and hot spring scale are subjected to a heat treatment or other process using a heat treatment machine, which is the ion raw material production means (w4), and used as an ion raw material containing one or more elements selected from the group consisting of Na, K, Ca, and Mg.
[0113] In the present embodiment, the carbonized material for the positive electrode active material (component (B)), the heavy oil (component (C)), and the sulfur (component (D)) used in the production of the positive electrode active material are not limited to those derived from the rubbers used as raw materials, and those produced from other raw materials or commercially available products may be added as necessary. However, it is preferable that at least a part of the carbonized material for the positive electrode active material (component (B)), heavy oil (component (C)), and sulfur (component (D)) used in the production of the positive electrode active material are obtained by the method for producing an electrode member of the present invention.
[0114] That is, in the manufacturing method of the electrode member of the present invention, it is preferable that at least a part of the carbonized material for the positive electrode active material (component (B)) is a refined carbonized material obtained by thermally decomposing a rubber containing sulfur to separate it into a solid and a dry distillation gas, selecting an unrefined carbonized material from the solid, and heat treating the unrefined carbonized material, that at least a part of the heavy oil (component (C)) is a heavy oil obtained by cooling the dry distillation gas to separate it into an oil and a gas, and distilling the oil to separate it into a heavy oil, a light oil, and sulfur, and that at least a part of the sulfur (component (D)) is sulfur obtained by distilling the oil to separate it into a heavy oil, a light oil, and sulfur.
[0115] In addition, in manufacturing the positive electrode active material, sulfides (particularly hydrogen sulfide) generated during heat treatment in the heat treatment means (z3) are desulfurized with an aqueous solution containing a neutralizing agent in a neutralizer, which is a neutralization means (w5), and sulfur content is recovered. In addition, a solid (neutralized solid) containing ions obtained by evaporating water from the aqueous solution containing the neutralizing agent used in the desulfurization can also be reused as an ion raw material.
[0116] Although the embodiment of the manufacturing method of the electrode member of the present invention has been described above with reference to the drawings, the embodiment disclosed herein is illustrative in all respects and is not restrictive. In particular, matters not explicitly disclosed in the embodiment disclosed herein, such as operating conditions, various parameters, dimensions, weights, volumes, etc. of components, do not deviate from the scope of ordinary practice by a person skilled in the art, and values that can be easily assumed by a person skilled in the art can be adopted.
[0117] <3-1. Positive electrode mixture> The positive electrode mixture of the present invention may be composed only of the positive electrode active material of the present invention, but in order to reduce the resistance inside the electrode, it may be mixed with a conductive material that is another conductive material (and other materials as necessary).
[0118] The conductive material has a role of improving electronic conductivity when an electrode is formed. The conductive material may be any material that has electrical conductivity (electronic conductivity) and does not impair the performance of the positive electrode active material of the present invention, and may be either an inorganic material or an organic material, but is typically a carbon-based material.
[0119] As the carbon-based material, any carbon-based material used in secondary batteries can be used, and more specific examples include graphite powder, carbon black (e.g., acetylene black, ketjen black, furnace black, etc.), fibrous carbon materials (carbon nanotubes, carbon nanofibers, vapor-grown carbon fibers, etc.), and the like. Among these, carbon black is a fine particle having a large surface area, and by adding it to a positive electrode mixture, it is possible to increase the electrical conductivity inside the obtained electrode and improve the charge / discharge efficiency and large current discharge characteristics.
[0120] Furthermore, the refined carbide explained in <2. Manufacturing method and manufacturing system for electrode member> can also be used as a carbon-based material as a conductive material.
[0121] The shape and size of the carbon-based material, which is a conductive material, can be appropriately selected taking into consideration the purpose of use of the electrode, etc., but when the carbon-based material is particulate, the particle size is, for example, 0.03 to 500 μm, and when it is fibrous, the diameter is 2 nm to 20 μm and the total length is about 0.03 to 500 μm.
[0122] The conductive material used in the present invention may be one type, or two or more types of conductive materials differing in size (particle size, fiber diameter, and fiber length), crystallinity, etc. may be used in any ratio.
[0123] The proportion of the conductive material in the positive electrode mixture can be appropriately selected taking into consideration the purpose of use of the electrode, etc., but when the conductive material is a carbon-based material, the proportion of the carbon-based material in the electrode is usually 5 to 100 parts by weight per 100 parts by weight of the electrode active material.
[0124] The positive electrode mixture of the present invention may contain other components within the scope of not impairing the object of the present invention. Typical examples of the other components include a binder.
[0125] The binder acts as a binding agent for adhering other electrode constituent materials. Examples of the binder include binders made of organic polymer compounds. Examples of the organic polymer compounds as binders include polysaccharides and derivatives thereof, such as methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl hydroxyethyl cellulose, and nitrocellulose; These include polyvinylidene fluoride (hereinafter sometimes referred to as PVDF), polytetrafluoroethylene (hereinafter sometimes referred to as PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, tetrafluoroethylene-perfluorovinyl ether copolymers; phenolic resins; melamine resins; polyurethane resins; urea resins; polyamide resins; polyimide resins; polyamide-imide resins; petroleum pitch; and coal pitch.
[0126] As the binder, a plurality of types of binders may be used.
[0127] The amount of the binder blended as a constituent material in the electrode is, for example, usually about 0.5 to 50 parts by weight, and preferably about 1 to 30 parts by weight, per 100 parts by weight of the total of the positive electrode active material and the conductive material.
[0128] <3-2. Negative electrode mixture> The negative electrode mixture of the present invention contains the refined carbide obtained by the above-mentioned production method as a negative electrode active material. The above-mentioned refined carbide is suitable as a negative electrode active material for a secondary battery, and a negative electrode formed from a negative electrode mixture containing the refined carbide becomes a high-performance negative electrode for a secondary battery.
[0129] The negative electrode mixture of the present invention may contain a carbon material other than the refined carbide, as long as the object of the present invention is not impaired.
[0130] The negative electrode mixture of the present invention may contain other components other than the carbon component within a range that does not impair the purpose. As the other components, a binder can typically be mentioned. As the binder, the same one that can be used for the positive electrode can be used, so the description of these is omitted.
[0131] <4. Secondary battery> One embodiment of the secondary battery of the present invention includes a positive electrode, a negative electrode, and an electrolyte, and is characterized in that the positive electrode is made using the above-mentioned positive electrode mixture of the present invention. Moreover, one embodiment of the secondary battery of the present invention includes a positive electrode, a negative electrode, and an electrolyte, and is characterized in that the negative electrode is made using the above-mentioned negative electrode mixture of the present invention. That is, the secondary battery of the present invention is characterized in that one or both of the positive electrode and negative electrode uses an electrode formed from the positive electrode mixture or negative electrode mixture of the present invention. The structure of the secondary battery of the present invention is not particularly limited, and any structure of a conventionally known secondary battery can be used, such as a stacked (flat) battery or a wound (cylindrical) battery.
[0132] Each component will be described below.
[0133] The positive electrode has a current collector and a positive electrode active material layer formed on the surface of the current collector, and the positive electrode active material layer is formed from the above-mentioned positive electrode mixture of the present invention (positive electrode active material, conductive material, and binder).
[0134] The current collector is not particularly limited and may be any known current collector, such as a foil, mesh, expanded grid (expanded metal), or punched metal made of a conductive material such as aluminum, nickel, copper, or stainless steel (SUS).
[0135] The size and thickness of the current collector are determined according to the intended use of the battery, and an appropriate size can be selected according to the size of the positive electrode to be used.
[0136] A typical method for producing a positive electrode is to mix a positive electrode mixture (positive electrode active material, conductive material, and binder) with a solvent to prepare a slurry, which is then coated onto a current collector, dried, and then pressed or otherwise fixed to form a positive electrode active material layer on the surface of the current collector, thereby obtaining a positive electrode.
[0137] Examples of the solvent for the slurry include amines such as N,N-dimethylaminopropylamine and diethyltriamine; ethers such as ethylene oxide and tetrahydrofuran; ketones such as methyl ethyl ketone; esters such as methyl acetate; and aprotic polar solvents such as dimethylacetamide and N-methyl-2-pyrrolidone. The method for applying the slurry to the current collector is not limited as long as it does not impair the object of the present invention, and examples of the method include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.
[0138] The negative electrode has a current collector and a negative electrode active material layer formed on a surface of the current collector. The negative electrode active material layer is typically formed of a negative electrode mixture containing a negative electrode active material.
[0139] Examples of the negative electrode active material include carbon materials such as natural graphite, artificial graphite, cokes, hard carbon, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies. The shape of the carbon material may be, for example, a flake shape such as natural graphite, a sphere shape such as mesocarbon microbeads, a fiber shape such as graphitized carbon fiber, or an aggregate of fine powder. Here, the carbon material may also function as a conductive material.
[0140] As described above, the negative electrode active material in the present invention is not limited to a specific one, but hard carbon may be used.
[0141] Hard carbon is a carbon material in which the stacking order hardly changes even when heat-treated at high temperatures of 2000°C or higher, and is also called non-graphitizable carbon. Examples of hard carbon include carbon fibers obtained by carbonizing infusible yarn, an intermediate product in the carbon fiber manufacturing process, at about 1000 to 1400°C, and carbon materials obtained by oxidizing an organic compound in air at about 150 to 300°C and then carbonizing it at about 1000 to 1400°C. The method for producing hard carbon is not particularly limited, and hard carbon produced by a conventional method can be used.
[0142] In one embodiment of the secondary battery of the present invention, it is preferable to use the refined carbide of the present invention described in <2. Manufacturing method and manufacturing system of electrode member> as the negative electrode active material. Note that the refined carbide may be the same as the component (B) in the positive electrode active material.
[0143] As the negative electrode active material, the above-mentioned carbon materials (including refined carbides) may be used alone or in combination of two or more kinds.
[0144] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably 80 to 95% by mass.
[0145] The binder can be the same as that for the positive electrode, so the explanation of these is omitted. The current collector is made of conductive materials such as aluminum, nickel, copper, and stainless steel (SUS). The current collector is made of foil, mesh, expanded grid (expanded metal), punched metal, etc., just like the current collector for the positive electrode.
[0146] As a method for forming the negative electrode active material layer on the current collector, the same method as the method for forming the positive electrode active material layer on the current collector can be adopted.
[0147] In the secondary battery of the present invention, the type of electrolyte is not particularly limited and can be selected as necessary. The electrolyte may be at least one selected from a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution). When the electrolyte is an electrolytic solution, the electrolytic solution contains an electrolyte salt and a non-aqueous solvent.
[0148] The electrolyte salt may be an electrolyte salt (for example, a sodium salt or a potassium salt) used in the secondary battery. One of the electrolyte salts may be used, or two or more of them may be used in combination.
[0149] As the non-aqueous solvent, a non-aqueous solvent used in a secondary battery can be used, and examples of the non-aqueous solvent include carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; ethers such as 1,2-dimethoxyethane and 1,3-dimethoxypropane; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; carbamates such as 3-methyl-2-oxazolidone; phosphates such as tris(2,2,2-trifluoroethyl)phosphate; and the above organic solvents further having a fluorine substituent introduced therein.
[0150] As a non-aqueous electrolyte solvent that has no flash point and is safe, phosphates are preferred, and tris(2,2,2-trifluoroethyl)phosphate is particularly preferred. Suitable examples of the electrolyte salt to be dissolved in the phosphate (particularly tris(2,2,2-trifluoroethyl)phosphate) include sodium bis(fluorosulfonyl)imide (NaFSI) and potassium bis(fluorosulfonyl)imide (KFSI) disclosed in the Examples. NaFSI is an electrolyte salt suitable for use when the ionic species (derived from component (A)) contained in the positive electrode active material of the present invention contains a large amount of sodium, while KFSI is an electrolyte salt suitable for use when the ionic species (derived from component (A)) contained in the positive electrode active material of the present invention contains a large amount of potassium and / or calcium.
[0151] A suitable example of the secondary battery of the present invention is a secondary battery formed using a positive electrode mixture containing the positive electrode active material obtained by the method for producing a positive electrode active material of the present invention. In addition, a preferred example of the secondary battery of the present invention is such that at least a part of the preferred example of the negative electrode active material is a refined carbonized material obtained by pyrolyzing a sulfur-containing rubber to separate it into a solid and a dry distillation gas, selecting an unrefined carbonized material from the solid, and heat-treating the unrefined carbonized material. In addition, in a preferred example of the secondary battery of the present invention, the electrolyte is preferably tris(2,2,2-trifluoroethyl)phosphate (TFEP) in which sodium bis(fluorosulfonyl)imide (NaFSI) or potassium bis(fluorosulfonyl)imide (KFSI) is dissolved as the electrolyte salt. EXAMPLES
[0152] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the following, "%" refers to "% by weight" unless otherwise specified.
[0153] (Experimental Example 1) The negative electrode was prepared as follows. The negative electrode active material used was "Renesis A1 (product number)," a refined carbonized material derived from waste tires. The refined carbonized material derived from waste tires, "Renesis A1 (product number)", is a refined carbonized material produced by the electrode component manufacturing system shown in FIG. 1 (referred to as "refined carbonized material of Experimental Example 1").
[0154] (Manufacturing method of "Renesis A1 (product number)" refined carbonized material derived from waste tires) The waste tires were heated at 400°C for 2 hours in an inert atmosphere container using nitrogen, and the components in the waste tires were gasified and cooled to convert them into oil (total of about 55% gasified and converted into oil), and the residue that was not gasified or converted into oil was collected, and the collected waste tire pyrolysis residue was further heat-treated, crushed to an average particle size of 20μm, and then magnetic material was completely removed using a 16,000 gauss electromagnetic separator to obtain an unrefined carbonized product derived from the waste tire pyrolysis residue. The obtained unrefined carbonized product was further subjected to supercritical processing and washing (CO2 washing) under the following conditions, and then heated at 850°C for 1 hour in an inert atmosphere container using argon, crushed and adjusted to particle size (0.2 to 100μm), to obtain a refined carbonized product. (Supercritical processing conditions) Supercritical fluid: Carbon dioxide (CO2) Set pressure: 20MPa Set temperature: 100℃ Processing time: 1 hour
[0155] 1.5 g (92.71% of the total) of the negative electrode active material (refined carbonized waste tires) and 0.106 g (6.55% of the total) of polyacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name 20CLPAH) as a binder were mixed in an aqueous solution containing 0.007 g of carboxymethylcellulose (CMC) and 0.005 g of CNTs as a solvent (Kusumoto Chemical Industries, Ltd. "TUBALL TM The mixture was mixed (kneaded) with 1.2 g of "BATT HO CMC" to obtain a negative electrode mixture. Next, the obtained negative electrode mixture was applied to an aluminum sheet (thickness 16 μm) that would become a negative electrode current collector, and dried at 70° C. for 3 hours to obtain a negative electrode sheet. A negative electrode having a diameter of 11.3 mm was cut out from the obtained negative electrode sheet.
[0156] The positive electrode active material of Experimental Example 1 was obtained by the following procedure. As the carbonized material for the positive electrode active material, "Renesis A1 (product number)" (the same as the negative electrode in Experimental Example 1), a refined carbonized material derived from waste tires, was used. 5.5 g (24.2% of the total raw materials) of the carbonized material for the positive electrode active material (component (B)), 8.44 g (37.2% of the total raw materials) of sodium percarbonate (component (A)), 2.75 g (12.1% of the total raw materials) of coal tar (component (C)), and 6 g (26.4% of the total raw materials) of sulfur (component (D)) were mixed in a stainless steel container and placed in a heating furnace. Nitrogen gas was introduced into the container to create an inert atmosphere, and heating was started 10 minutes later. The temperature was raised to 300°C in 50 minutes, and heating was continued even after reaching 300°C, and stopped at 350°C. After that, the temperature dropped to 200°C, and the product was removed from the heating furnace and allowed to cool naturally. After the temperature inside the container dropped to 50°C or less, the synthesized product was taken out. The weight of the synthesized product was 15.2 g. The synthesized product was pulverized in a mixer to obtain a positive electrode active material of Experimental Example 2 consisting of a powder with an average particle size of 20 μm. It was confirmed by physical property evaluation that the positive electrode active material of Experimental Example 1 contained sodium thiosulfate.
[0157] The positive electrode of Experimental Example 1 was obtained as follows. 2 g (94.49% of the total) of the positive electrode active material of Experimental Example 1 and 0.056 g (2.64% of the total) of acetylene black (AB, Denki Kagaku Kogyo Co., Ltd. (HS100)) as a conductive material were mixed (kneaded) uniformly into 0.673 g of NMP solvent (CNT was substantially 0.003 g, solid content ratio 0.08%) containing 0.058 g (2.71% of the total) of PVDF to obtain a positive electrode mixture of Experimental Example 1. Next, the obtained positive electrode mixture was applied to an aluminum sheet (thickness 16 μm) that becomes a positive electrode current collector, and dried at 50 ° C for 3 hours to obtain a positive electrode sheet. A 15 mm φ was cut out from the obtained positive electrode sheet to obtain the positive electrode of Experimental Example 1.
[0158] The obtained positive and negative electrodes were combined with an electrolyte solution of tris(2,2,2-trifluoroethyl)phosphate (TFEP) in which sodium bis(fluorosulfonyl)imide (NaFSI) was dissolved at 2 mol / L as a sodium salt (hereinafter referred to as "NaFSI / TFEP") and a separator of Celgard 2400 to obtain a battery of Experimental Example 1 (a coin-type battery (cylindrical, outer diameter 20 mm / height 3.2 mm), hereinafter referred to as "coin-type battery (R2032)").
[0159] Using the battery of Experimental Example 1 above, a charge / discharge test was carried out under the following conditions while maintaining the temperature at 25°C. (Cell configuration) 2-pole type Positive electrode: An electrode containing a positive electrode active material Negative electrode: An electrode containing a negative electrode active material Electrolyte: 2M NaFSI / TFEP (Charge / discharge conditions) Voltage range: 0.5-3.9V Charging was performed using CVCC charging, in which a constant current was applied up to 3.9 V, followed by a current sufficient to maintain the voltage for 5 hours, at which point the current value decreased.
[0160] The results of the charge / discharge test of the battery of Experimental Example 1 are as follows. 73.5μA / 1.766cm 2 (Positive electrode 15mmφ) Number of charge / discharge cycles: 20 Discharge time: Approximately 4 hours (73.5μAh)
[0161] To confirm the voltage retention of the battery of Experimental Example 1, after 20 charge / discharge cycles, the battery was charged to 3.9V, and the voltage was evaluated 5 minutes after charging was stopped, resulting in a voltage of 3.80V.
[0162] As described above, it was confirmed that a chargeable and dischargeable secondary battery can be produced using a positive electrode active material obtained by heat-treating sodium percarbonate (component (A)), carbonized material for positive electrode active material (component (B)), coal tar (component (C)), and sulfur (component (D)) under an inert gas atmosphere.
[0163] (Experimental Example 2) The positive electrode active material of Experimental Example 2 was obtained by the following procedure. As the carbonized material for the positive electrode active material, "Renesis A1 (product number)" (the same as the negative electrode in Experimental Example 1), a refined carbonized material derived from waste tires, was used. A total of 48.8 g of the carbonized material for the positive electrode active material (component (B)) (20% of the total raw materials), 25 g of potassium hydrogen carbonate (component (A)) (51% of the total raw materials), 3.8 g of coal tar (component (C)) (8% of the total raw materials), and 10 g of sulfur (component (D)) (20% of the total raw materials) were mixed in a stainless steel container and placed in a heating furnace. Nitrogen gas was passed through the container to create an inert atmosphere, and heating was started 10 minutes later. The temperature was raised to 300°C in 50 minutes, and heating was continued even after reaching 300°C, and stopped at 350°C. After that, the temperature dropped to 200°C, and the product was removed from the heating furnace and allowed to cool naturally. The synthesis product was taken out after the temperature inside the container became 50°C or lower. The weight of the synthesized product was 32.5 g, which was a yield of 67%. The synthesized product was pulverized in a mixer to obtain a positive electrode active material of Experimental Example 2 consisting of a powder with an average particle size of 20 μm. It was confirmed by physical property evaluation that the positive electrode active material of Experimental Example 2 contained potassium thiosulfate.
[0164] A positive electrode mixture of Experimental Example 2 was obtained by uniformly mixing (kneading) 1.003 g (86% of the total) of the positive electrode active material of Experimental Example 2 and 0.063 g (5.41% of the total) of AB as a conductive material with 2.453 g of NMP solvent (CNT was essentially 0.025 g, solid content ratio 2.14%) containing 0.073 g (6.27% of the total). Next, the obtained positive electrode mixture was applied to an aluminum sheet (thickness 16 μm) serving as a positive electrode current collector, and dried at 50° C. for 3 hours to obtain a positive electrode sheet. A piece of 15 mmφ was cut out from the obtained positive electrode sheet to provide the positive electrode of Experimental Example 2.
[0165] The negative electrode was prepared in the same manner as in Experimental Example 1.
[0166] The obtained positive and negative electrodes were combined with an electrolyte solution of tris(2,2,2-trifluoroethyl)phosphate (TFEP) with potassium bis(fluorosulfonyl)imide (KFSI) as a potassium salt dissolved at 2 mol / L (hereinafter referred to as "KFSI / TFEP") and Celgard 2400 as a separator to obtain a battery of Experimental Example 2 (coin-type battery (R2032)).
[0167] Using the battery of Experimental Example 2 described above, a charge / discharge test was carried out under the following conditions while maintaining the temperature at 25°C. (Cell configuration) 2-pole type Positive electrode: An electrode containing a positive electrode active material Negative electrode: An electrode containing a negative electrode active material Electrolyte: 2M KFSI / TFEP (Charge / discharge conditions) Voltage range: 2.0-4.2V Charging was performed using CVCC charging, in which a constant current was applied up to 4.2 V, followed by a current sufficient to maintain the voltage for 5 hours, at which point the current value decreased.
[0168] The results of the charge / discharge test are as follows. 64.7μA / 1.766cm 2 (Positive electrode 15mmφ) Number of charge / discharge cycles: 5 times Discharge time: Approximately 5 hours (64.7μAh)
[0169] As described above, it was confirmed that a chargeable and dischargeable secondary battery can be produced using a positive electrode active material obtained by heat-treating potassium bicarbonate (component (A)), carbonized material for the positive electrode active material (component (B)), coal tar (component (C)), and sulfur (component (D)) under an inert gas atmosphere.
[0170] (Experimental Example 3) The positive electrode active material of Experimental Example 3 was obtained by the following procedure. Wood combustion ash (plant combustion ash) obtained by burning wood (camellia tree) in air using a heating furnace was used as component (A). In addition, refined carbonized material derived from waste tires, "Renesis A1 (product number)" (the same as the negative electrode in Experimental Example 1), was used as the carbonized material for the positive electrode active material (component (B)). A total of 30.7 g of raw materials, consisting of 12.7 g (41% of the total raw materials) of wood combustion ash (component (A)), 6 g (20% of the total raw materials) of carbonized material for positive electrode active material (component (B)), 3 g of coal tar (10% of the total raw materials), and 9 g of sulfur (29% of the total raw materials), were mixed in a stainless steel container and placed in a heating furnace. Nitrogen gas was introduced into the container to create an inert atmosphere, and heating was started 10 minutes later. The temperature was raised to 300°C in 50 minutes, and heating continued even after reaching 300°C, stopping at 350°C. After that, the temperature dropped to 200°C, and the container was removed from the heating furnace and naturally cooled. After the temperature inside the container reached 50°C or less, the synthesized product was taken out. The weight of the synthesized product was 21.9 g, which was a yield of 71%. The synthesized product was pulverized in a mixer to obtain a positive electrode active material of Experimental Example 3 consisting of a powder with an average particle size of 20 μm.
[0171] The positive electrode mixture of Experimental Example 3 was obtained by uniformly mixing (kneading) 1.14 g of the positive electrode active material of Experimental Example 3 and 0.08 g of AB as a conductive material in 2.453 g of NMP solvent containing 0.073 g of PVDF (CNT was essentially 0.025 g, solid content ratio 2.14%). Next, the obtained positive electrode mixture was applied to an aluminum sheet (thickness 16 μm) serving as a positive electrode current collector, and dried at 50° C. for 3 hours to obtain a positive electrode sheet. A piece of 12.9 mmφ was cut out from the obtained positive electrode sheet to provide the positive electrode of Experimental Example 3.
[0172] The negative electrode was prepared in the same manner as in Experimental Example 1.
[0173] The obtained positive and negative electrodes were combined with tris(2,2,2-trifluoroethyl)phosphate (TFEP) as an electrolyte, potassium bis(fluorosulfonyl)imide (KFSI) as a potassium salt dissolved at 2 mol / L (KFSI / TFEP), and Celgard 2400 as a separator to obtain a battery of Experimental Example 3 (coin-type battery (R2032)).
[0174] Using the battery of Experimental Example 3, a charge / discharge test was carried out under the following conditions at a temperature of 25°C. (Cell configuration) 2-pole type Positive electrode: An electrode containing a positive electrode active material Negative electrode: An electrode containing a negative electrode active material Electrolyte: 2M KFSI / TFEP (Charge / discharge conditions) Voltage range: 1.2-3.8V CVCC charge, CC discharge (The initial voltage retention CV is 30 hours, the second 10 hours, and the third and subsequent 5 hours)
[0175] The results of the charge / discharge test of the battery of Experimental Example 3 are as follows. 112μA / 1.306cm 2 (Positive electrode 12.9mmφ) Number of charge / discharge cycles: 27 Discharge time: Approximately 1 hour (112μAh)
[0176] As described above, it was confirmed that a rechargeable secondary battery can be produced using a positive electrode active material obtained by heat-treating wood combustion ash (component (A)), carbonized material for the positive electrode active material (component (B)), coal tar (component (C)), and sulfur (component (D)) under an inert gas atmosphere.
[0177] (Experimental Example 4) The positive electrode active material of Experimental Example 4 was obtained by the following procedure. Eggshell calcined material (main component: CaO) obtained by heat-treating eggshells at 1200°C in a heating furnace was used as component (A). In addition, refined carbide made from waste tires, "Renesis A1 (product number)" (the same as the negative electrode in Experimental Example 1), was used as the carbide for the positive electrode active material (component (B)). A total of 48.8 g of raw materials, consisting of 25 g (51% of the total raw materials) of baked eggshell (component (A)), 10 g (20% of the total raw materials) of carbonized material for positive electrode active material (component (B)), 3.8 g of coal tar (8% of the total raw materials), and 10 g of sulfur (20% of the total raw materials), were kneaded in a stainless steel container and put into a heating furnace. Nitrogen gas was introduced into the container to create an inert atmosphere, and heating was started 10 minutes later. The temperature was raised to 300°C in 50 minutes, and heating was continued even after reaching 300°C, and stopped at 350°C. After that, the temperature dropped to 200°C, and the container was taken out of the heating furnace and naturally cooled. After the temperature inside the container became 50°C or less, the synthesized product was taken out. The weight of the synthesized product was 32.5 g, which was a yield of 67%. The synthesized product was pulverized in a mixer to obtain a positive electrode active material of Experimental Example 4 consisting of a powder with an average particle size of 20 μm.
[0178] The positive electrode active material of Experimental Example 4 (4.015 g) and AB (0.08 g) as a conductive material were uniformly mixed (kneaded) into 2.453 g of NMP solvent (CNT was essentially 0.025 g, solid content ratio 2.14%) containing 0.073 g of PVDF, to obtain a positive electrode mixture of Experimental Example 4. Next, the obtained positive electrode mixture was applied to an aluminum sheet (thickness 16 μm) serving as a positive electrode current collector, and dried at 50° C. for 3 hours to obtain a positive electrode sheet. A piece of 11.3 mmφ was cut out from the obtained positive electrode sheet to provide the positive electrode of Experimental Example 4.
[0179] The negative electrode was prepared in the same manner as in Experimental Example 1.
[0180] The obtained positive and negative electrodes were combined with tris(2,2,2-trifluoroethyl)phosphate (TFEP) as an electrolyte, potassium bis(fluorosulfonyl)imide (KFSI) as a potassium salt dissolved at 2 mol / L (KFSI / TFEP), and Celgard 2400 as a separator to obtain a battery of Experimental Example 4 (coin-type battery (R2032)).
[0181] Using the battery of Experimental Example 4, a charge / discharge test was carried out under the following conditions at a temperature of 25°C. (Cell configuration) 2-pole type Positive electrode: An electrode containing a positive electrode active material Negative electrode: An electrode containing a negative electrode active material Electrolyte: 2M KFSI / TFEP (Charge / discharge conditions) Voltage range: 1.2-3.8V CVCC charge, CC discharge (The initial voltage retention CV is 30 hours, the second 10 hours, and the third and subsequent 5 hours)
[0182] The results of the charge / discharge test of the battery of Experimental Example 4 are as follows. 112μA / 1cm 2 (Positive electrode 11.3mmφ) Number of charge / discharge cycles: 48 Discharge time: Approximately 1 hour (75μAh)
[0183] (Experimental Example 5) The negative electrode was manufactured in the same manner as in Experimental Example 1, except that a refined carbonized material produced by the manufacturing method described below ("Renesis A2 (product number)") was used instead of the refined carbonized material derived from waste tires "Renesis A1 (product number)" used as the negative electrode active material in Experimental Example 1. The refined carbonized material derived from waste tires, "Renesis A2 (product number)", is a refined carbonized material produced by the electrode component manufacturing system shown in FIG. 1 (referred to as "refined carbonized material of Experimental Example 5").
[0184] (Manufacturing method of "Renesis A2 (product number)" refined carbonized material derived from waste tires) The waste tires were heated at 400°C for 2 hours in an inert atmosphere container using nitrogen, and the components in the waste tires were gasified and cooled to be converted to oil (total of about 55% gasified and converted to oil), and the residue that was not gasified or converted to oil was collected, and the collected waste tire pyrolysis residue was further heat-treated, pulverized to an average particle size of 20μm, and then magnetic material was completely removed using a 16,000 gauss electromagnetic separator to obtain an unrefined carbonized product derived from the waste tire pyrolysis residue. The obtained unrefined carbonized product was further subjected to supercritical treatment and cleaning under the following conditions, and then heated at 850°C for 1 hour in an inert atmosphere container using argon, pulverized, and sieved to adjust the particle size (10 to 30μm) to obtain a refined carbonized product. (Supercritical processing conditions) Supercritical fluids: Carbon dioxide (CO2) and isopropyl alcohol (IPA) CO2:IPA=8:1 (volume ratio when liquid) Set pressure: 8.5MPa Set temperature: 300℃ Processing time: 1 hour
[0185] (Cathode and battery manufacturing) A battery (coin-type battery (R2032)) of Experimental Example 5 was obtained in the same manner as Experimental Example 1, except that the refined carbide "Renesis A2 (product number)" produced by the above-mentioned manufacturing method was used instead of the refined carbide "Renesis A1 (product number)" as the negative electrode active material. That is, the negative electrode in the battery of Experimental Example 5 uses a refined carbide ("Renesis A2 (product number)"), and the other components (positive electrode, electrolyte, electrolyte salt, separator, etc.) are the same as those of Experimental Example 1.
[0186] Using the battery of Experimental Example 5 above, a charge / discharge test was carried out under the following conditions while maintaining the temperature at 25°C. (Cell configuration) 2-pole type Positive electrode: An electrode containing a positive electrode active material Negative electrode: An electrode containing a negative electrode active material Electrolyte: 2M NaFSI / TFEP (Charge / discharge conditions) Voltage range: 0.5-3.9V Charging was performed using CVCC charging, in which a constant current was applied up to 3.9 V, followed by a current sufficient to maintain the voltage for 5 hours, at which point the current value decreased.
[0187] The results of the charge / discharge test of the battery of Experimental Example 5 are as follows. 85μA / 1.306cm 2 (Positive electrode 12.9mmφ) Charge / discharge count: 60 times Discharge time: Approx. 2 hours (85μAh)
[0188] In order to confirm the voltage retention of the battery of Experimental Example 5, after 60 charge / discharge cycles, the battery was charged to 3.9V, and the voltage was evaluated 5 minutes after charging was stopped, resulting in a voltage of 3.88V. In other words, the battery of Experimental Example 5, which used the refined carbonized material of Experimental Example 5 (Renesis A2) instead of the refined carbonized material of Experimental Example 1 (Renesis A1), exhibited a superior voltage retention capability to the voltage retention capability of the battery of Experimental Example 1 described above (3.80 V after 60 charge / discharge cycles). [Industrial Applicability]
[0189] The present invention can provide a secondary battery using inexpensive materials without using lithium, and therefore the present invention is extremely useful industrially. [Explanation of symbols]
[0190] x Heat treatment method y1 Selection method y2 Cleaning method y3 Heat treatment method z1 Separation means z2 kneading means z3 Heat treatment method z4 adjustment means w1 Gas treatment means w2 Combustion means w3 Crushing method w4 Ion raw material production means w5 Neutralization method
Claims
1. A method for producing a refined charcoal using sulfur-containing rubbers as a raw material, the method comprising the steps of: (1) pyrolyzing the raw material and separating it into a solid and a dry distillation gas; (2) separating an unrefined charcoal from the solid; and (3) subjecting the unrefined charcoal to subcritical or supercritical treatment, followed by heat treatment in a non-oxidizing atmosphere, to obtain a refined charcoal.
2. 2. The method for producing refined charcoal according to claim 1, wherein the sulfur-containing rubber is rubber derived from tires.
3. The method for producing refined carbonized material according to claim 2, wherein the rubber derived from tires is tire dust.
4. 2. The method for producing refined charcoal according to claim 1, wherein the supercritical fluid used in the subcritical or supercritical treatment in step (3) is carbon dioxide.
5. 2. The method for producing purified charcoal according to claim 1, wherein the supercritical fluid used in the subcritical or supercritical treatment in step (3) is a mixture of carbon dioxide and an alcohol having 3 or less carbon atoms.
6. The method for producing purified charcoal according to claim 5, wherein the alcohol having 3 or less carbon atoms is isopropanol.
7. 2. The method for producing refined carbide according to claim 1, wherein the temperature of the heat treatment in the non-oxidizing atmosphere in the step (3) is 650° C. or higher and 1000° C. or lower.
8. 2. The method for producing refined carbide according to claim 1, further comprising a step of pulverizing and sieving the refined carbide after the heat treatment in a non-oxidizing atmosphere in the step (3).
9. A refined carbide obtained by the method according to any one of claims 1 to 8.
10. The refined carbide according to claim 9, having a particle size range of 5 μm to 60 μm.
11. A negative electrode mixture comprising the refined carbide according to claim 9 as a negative electrode active material.
12. A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, the negative electrode being formed using the negative electrode mixture according to claim 11.
13. A method for producing sulfur using sulfur-containing rubbers as a raw material, the method comprising: a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas; and a step (4) of cooling the dry distillation gas to separate it into an oil component and a gas, and distilling the oil component to separate it into a heavy oil, a light oil, and sulfur.
14. A method for producing heavy oil and / or light oil using sulfur-containing rubbers as a raw material, comprising: a step (1) of thermally decomposing the raw material to separate it into a solid and a dry distillation gas; and a step (4) of cooling the dry distillation gas to separate it into an oil fraction and a gas, and distilling the oil fraction to separate it into a heavy oil, a light oil, and sulfur.
Citation Information
Patent Citations
Vulcanization accelerating composition
JP1980034227A
Manufacture of circuit module
JP1987066655A
Nonaqueous electrolyte secondary battery cathode active material and manufacturing method thereof and nonaqueous electrolyte secondary battery
JP2013101811A
Charcoal refining method
JP2021521323A